Earth Science Education 3. Evolution of the Calgary Science Network: An Unabashed Tale of Speciation, Extinction and Diversity - Nowlan, Godfrey; Neale, E. R. (Geoscience Canada, 2000)
Summary Activities undertaken by the Calgary Science Network to promote the public awareness of science over more than a decade are described in an evolutionary paradigm. The Network is a charitable volunteer organization that has an impressive history of accomplishment. The many different projects and programs of the Network are described in an evolutionary framework that has two fundamental generic roots: one in the Science Hotline, the other in the now-defunct National Science and Technology Week. The strong multidisciplinary background of the organization is cited as a key to its success.